2016
DOI: 10.1002/ajmg.a.37574
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of hypophosphatemic rickets in generalized arterial calcification of infancy (GACI) without worsening of vascular calcification

Abstract: Patients with generalized arterial calcification of infancy (GACI) develop vascular calcifications early in life. About half of them die within the first six months despite optimal medical care. A subset of those who survive eventually develop hypophosphatemic rickets. Since hypophosphatemia and hyperphosphaturia have been previously associated with increased survival in GACI patients, physicians often avoid phosphate repletion as treatment for rickets. As a consequence, GACI patients develop severe rachitic c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 11 publications
2
26
0
Order By: Relevance
“…Interestingly, ENPP1 knockdown related accelerated proliferation in VSMCs could not be inhibited by the addition of PP i or bisphosphonates, i.e., the synthetic analogues of PP i , indicating a mechanism that is independent of ENPP1-mediated extracellular PP i concentration. This result is in accordance with clinical studies in GACI individuals showing that treatment with bisphosphonates increases the rate of survival, but has no influence on intimal proliferation or vascular stenosis in ENPP1-deficient patients 1 , 6 , 33 . Recently, it has been shown that the treatment of Enpp1 asj/asj mice with recombinant ENPP1 elevated extracellular PP i levels and inhibited arterial calcification 21 .…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Interestingly, ENPP1 knockdown related accelerated proliferation in VSMCs could not be inhibited by the addition of PP i or bisphosphonates, i.e., the synthetic analogues of PP i , indicating a mechanism that is independent of ENPP1-mediated extracellular PP i concentration. This result is in accordance with clinical studies in GACI individuals showing that treatment with bisphosphonates increases the rate of survival, but has no influence on intimal proliferation or vascular stenosis in ENPP1-deficient patients 1 , 6 , 33 . Recently, it has been shown that the treatment of Enpp1 asj/asj mice with recombinant ENPP1 elevated extracellular PP i levels and inhibited arterial calcification 21 .…”
Section: Discussionsupporting
confidence: 91%
“…Especially in recent years, different approaches for treating GACI have been intensively investigated, including early generation bisphosphonates 6 , 28 , 29 , orally administered PP i 20 and soluble recombinant ENPP1-Fc protein 21 . However, all of these studies focused on treating arterial calcification, while the most prominent complications for GACI patients are severe congestive cardiac failure, hypertension and myocardial ischemia due to myointimal proliferation and arterial stenosis 1 , 6 . In our literature survey, approximately 72% of published GACI cases display intimal hyperplasia and/or arterial stenoses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, subjects 1 to 4 showed no signs of rachitic dental manifestations. Subject 5 presented unusual cusp patterns and a history of extensive sealant application, as noted previously (Ferreira et al 2016). While these observations are consistent with very mild enamel effects, in isolation they are not strong evidence of rachitic teeth.…”
Section: Additional Dental Manifestations Of Gacisupporting
confidence: 70%
“…48,49 Indeed, both decreased and increased bone turnover are shown to accelerate VC process. 50,51 In this regard, decreased mineralization in the bone of uremic PiT-2 HET mice fed a high P diet might have contributed to the enhanced VC in our study. However, it still remains unclear which bone cells were affected by PiT-2 deficiency and how PiT-2 deficiency altered bone metabolism.…”
Section: Discussionmentioning
confidence: 65%